Critically Analyzing the Online Classroom: Blackboard, Moodle, Canvas, and the Pedagogy They Produce - J.D. Swerzenski (Central States Communication Association, 2021)
Working from the crossroads of critical pedagogy and software studies, this study analyzes the means by which teaching technologies-in particular the popular learning management systems (LMS) Blackboard, Moodle, and Canvas-support a transmission model of education at the expense of critical learning goals. I assess the effect of LMSs on critical aims via four key critical pedagogy concepts: the banking system, student/teacher contradiction, dialogue, and problem-posing. From software studies, I employ the notion of affordances-what program functions are and are not made available to users-to observe how LMSs naturalize the transmission model. Rather than present a deterministic look at teaching technology, this study calls for closer examination of these tools in order to rework teaching technologies toward critical ends.